IMPLEMENTASI FAKTOR KEGAGALAN KINERJA PROYEK PADA PROYEK-PROYEK DI X PROYEK JAWA TIMUR - Permana, Hieka Wahyu; Suyoso, Aldo Lovely Arief; Agustina, Tri Siwi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The types of projects include, public school building procurement projects, procurement of main transmission materials, relocation and various other projects. This infrastructure will support services for additional students for the next ten years so ​​that a comprehensive implementation of project performance failure management analysis is needed to be able to identify, analyze, evaluate, and respond to project failure risks so that project work runs well. The following is data related to the procurement of goods and services projects associated with monitoring results during the project.This study examines the effect of project external environment and construction material supply related problems on project performance failure through ineffective contract management on building construction projects. This study uses a quantitative method with SEM-PLS (Structural Equation Modeling) Partial Least Square analysis. The results of the study indicate that project external environment and construction material supply related problems affect project performance failure through ineffective contract management on building construction projects.